Optimal airfoil in an inverse problem of jet aerodynamics - Lupu, Mircea; Scheiber, Ernest (Computer Assisted Methods in Engineering and Science, 2023)
The paper deals with a special inverse boundary problem, when the boundary of the domain is completely unknown and a singular integral equation for the velocity angle is obtained. For the model of free plane symmetric incompressible jet forked by an airfoil, the boundary equations and airfoil shape are "a posteriori" determined, while the velocity along them is "a priori" prescribed. With the aim to obtain minimum drag, in the present paper there is solved the optimization problem for airfoils, using the penalty method and the golden section method. In the case of optimum, numerical computations are performed and the airfoil design together with the drag coefficient are obtained.